L’INTERCULTUREL, UNE COMPOSANTE PARMI D’AUTRES DE LA COMPÉTENCE CULTURELLE - Puren, Christian (Neofilolog, 2019)
Interculturality, only one of the components of cultural competence The notion of interculturality has occupied the entire field of reflection on culture in the didactics of languages and cultures during the past decades. Unduly, because intercultural competence is in reality only one of the components of cultural competence. Pluricultural compe-tence, for example, was introduced in the years 2000-2001 in the Com-mon European Framework of Reference for Languages: Learning, teach-ing, assessment (Council of Europe, 2001), but the other components that preceded it during the evolution of the discipline – the transcul-tural and metacultural components – are just as essential. Also, a new « co-cultural » component had to be mobilized later in the elaboration of the action-oriented approach which is outlined in this document. In the epistemological framework of the complex didactics of languages-cultures, which are as attentive to the diversity of audiences and the objectives and environments of learning and teaching processes, as to the challenges of social action training, all these components must now be simultaneously taken into account.